2016
DOI: 10.1111/jcom.12231
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasive Force of Political Humor

Abstract: Political humor is ubiquitous in some contexts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…While political satire has been a feature of U.S. political life since the days of the American Revolution, the effects of exposure to satirical content has been a consistent focus of research for the past 20 years (Becker and Waisanen, ). This research suggests that political satire shapes a wealth of outcomes, including media habits and choices, attitudes toward politicians, interest in the political process, knowledge about politics, and the desire to participate and engage both civically and politically (Baek and Wojcieszak, ; Baum, ; Baumgartner and Lockerbie, ; Baumgartner and Morris, ; Becker and Bode, ; Cao, ; Feldman and Young, ; Hoffman and Young, ), although effects vary for different populations (Boukes et al., ; Innocenti and Miller, ). On balance, research has also shown that political comedy is seen as both a source of news and entertainment, often offers as much factual and contextual information as traditional network news programming, and can present a space for a more deliberative conversation about politics and public affairs than is currently offered on cable television news networks (Baym, ; Becker, ; Fox, Koloen, and Sahin, ; LaMarre et al., ; Purcell, Heitmeier, and Van Wyhe, ; Young, ).…”
mentioning
confidence: 99%
“…While political satire has been a feature of U.S. political life since the days of the American Revolution, the effects of exposure to satirical content has been a consistent focus of research for the past 20 years (Becker and Waisanen, ). This research suggests that political satire shapes a wealth of outcomes, including media habits and choices, attitudes toward politicians, interest in the political process, knowledge about politics, and the desire to participate and engage both civically and politically (Baek and Wojcieszak, ; Baum, ; Baumgartner and Lockerbie, ; Baumgartner and Morris, ; Becker and Bode, ; Cao, ; Feldman and Young, ; Hoffman and Young, ), although effects vary for different populations (Boukes et al., ; Innocenti and Miller, ). On balance, research has also shown that political comedy is seen as both a source of news and entertainment, often offers as much factual and contextual information as traditional network news programming, and can present a space for a more deliberative conversation about politics and public affairs than is currently offered on cable television news networks (Baym, ; Becker, ; Fox, Koloen, and Sahin, ; LaMarre et al., ; Purcell, Heitmeier, and Van Wyhe, ; Young, ).…”
mentioning
confidence: 99%
“…However, as discussed above in relation to Innocenti and Miller (2016), humor across social groups works persuasively only to the extent that boundaries between them are not fixed. Indeed, rather than ridiculing their own ethnicity or the ethnicity of others, participants in Ali and Husu seem to ridicule stereotypes themselves.…”
Section: Humor In Practice: Textual Analysismentioning
confidence: 99%
“…Normative pragmatic theories (e.g., Goodwin 2001Goodwin , 2007Goodwin , 2011Innocenti 2011;Innocenti and Miller 2016;Jacobs 2000Jacobs , 2016Kauffeld 1998Kauffeld , 2001Kauffeld , 2009van Eemeren et al 2014) have explained why speech acts may reasonably be expected to influence addressees just as the speaker intends. The theories are "normative" because they locate persuasive force in norms that message designs bring to bear in a situation, and "pragmatic" because they account for the persuasive force of actual message designs.…”
Section: Basic Normative Pragmatic Modelmentioning
confidence: 99%
“…Drawing on normative pragmatic theory (e.g., Goodwin 2001Goodwin , 2007Goodwin , 2011Innocenti 2011;Innocenti and Miller 2016;Jacobs 2000Jacobs , 2016Kauffeld 1998Kauffeld , 2001Kauffeld , 2009van Eemeren et al 2014), we argue that the normative structure of demanding involves speakers (1) openly making visible (a) their intent to influence addressees to accede, thereby (b) incurring an obligation to live up to a norm captured by the aphorism "right makes might." (2) The obligation is reciprocal; both speakers and addressees can hold each other accountable for recognizing and living up to the norm.…”
mentioning
confidence: 99%
See 1 more Smart Citation